Clinical outcomes and treatment patterns of primary central nervous system lymphoma: Multicenter retrospective analysis - Güven, Serkan; Yavuz, Boran; Erdoğan Yücel, Elçin; Karataş, Aylin Fatma; Özsan, Güner Hayri; Demirkan, Fatih; Ündar, Bülent; Özcan, Mehmet Ali; Kiper, Hatice Demet; Çetintepe, Tuğba; Göçer, Mesut; Kurtoğlu, Erdal; et al. (Kare Publishing, 2023)
Objectives: Primary central nervous system lymphoma (PCNSL) is a rare malignant disease with poor prognosis. Its low incidence leads to challenges in decision-making for treatment. As a matter of fact, there is still no consensus on the appropriate treatment modalities. In this context, the objective of this study is to investigate and comparatively assess the efficacies of several treatment modalities in the treatment of PCNSL. Methods: Thirty-four patients diagnosed with PCNSL at 5 different hematology centers between 2007 and 2021 were included in the study. Patients’ data from all five centers were collected retrospectively. Since ibrutinib is not approved for this indication in Turkey, consent for off-label use of ibrutinib is obtained from each patient. Ethics committee ap-proval was obtained on June 9, 2021 with decision number 2021/18-05. Results: The median age of the patients was 59 (min.: 22, max.: 78) years. The male-to-female ratio was 1.26/1. Nineteen (55.9%) patients had Eastern Cooperative Oncology Group (ECOG) performance score of ?2. Fifteen (44.1%) patients had normal lactate dehydrogenase (LDH) levels and only 14.7% of the patients had B symptoms at the time of diagnosis. Magnetic resonance imaging (MRI) revealed a single mass lesion in 14 (41.2%) patients. As an induction therapy, meth-otrexate-based regimen was administered in 29 (85.3%) patients. Only 14 of the 34 patients received 4 or more cycles of high-dose methotrexate (MTX). About 32.4% of the patients received radiation therapy (RT) during follow-up as a part of induction therapy. Five patients received only RT due to poor performance status. Ibrutinib was administered in 5 patients for refractory disease. It was determined that four or more cycles of MTX treatment increased progression-free survival (PFS) (p=0.031) and overall survival (OS) (p=0.012). Moreover, RT improved PFS (p=0.023). Considering that the complete response achieved by induction therapy influences long-term survival, achievement of the best response to the treatment regimens administered in combination with new agents may prolong survival (PFS: p=0.01, OS: p=0.023). Conclusion: The findings of this study indicate that the initial response to treatment is crucial. Additionally, it was found that high-dose MTX treatment should be administered for 4 cycles or more in order to achieve the best results. Furthermore, it was determined that ibrutinib monotherapy was well-tolerated in our patients with relapsed/refractory disease, with excellent clinical benefits. In conclusion, a combination therapy consisting of high-dose MTX, ibrutinib, and rituximab appears to be a promising initial treatment approach in appropriate patients.
Keywords: Ibrutinib; Methotrexate; PCNSL; Radiotherapy